A Review of the Use of Methadone for the Treatment of Chronic Noncancer Pain - Mary E Lynch (Pain Research and Management)
Methadone, although having been available for approximately half a century, is now receiving increasing attention in the management of chronic pain. This is due to recent research showing that methadone exhibits at least three different mechanisms of action including potent opioid agonism, N-methyl-D-aspartate antagonism and monoaminergic effects. This, along with methadone's excellent oral and rectal absorption, high bioavailability, long duration of action and low cost, make it a very attractive option for the treatment of chronic pain. The disadvantages of significant interindividual variation in pharmacokinetics, graduated dose equivalency ratios based on prerotation opioid dose when switching from another opioid, and the requirement for special exemption for prescribing methadone make it more complicated to use. The present review is intended to educate physicians interested in adding methadone to their armamentarium for assisting patients with moderate to severe pain.